PENGARUH INTELLECTUAL CAPITAL TERHADAP ASSET QUALITY PERBANKAN INDONESIA - Khotari, Hary Rafi; Sadikin, Dikdik Saleh (Journal of Accounting, Management and Islamic Economics, 2024)
The purpose of this study was to examine the effect of intellectual capital on the quality of assets of banks in Indonesia listed on the Indonesia Stock Exchange for the period 2015-2019 with credit collectability and log size as control variables. The sample selection in this study used a purposive sampling method and resulted in a sample of 7 Conventional Banks Book IV in banks listed on the Indonesia Stock Exchange during the 2014-2019 period. The analysis technique used in this research is multiple linear regression analysis. The hypothesis in this study is based on previous research and various other supporting theories. The findings in this study provide a positive effect on asset quality. Based on research results. Our suggestions in this study include that Bank Indonesia and the Financial Services Authority need to strengthen monitoring and control of banking operations to ensure that IC components are complementary. The regulations, policies and directives regarding HC, SC, and CE that are used must be synchronized or harmonized to ensure the improvement of the quality of banking assets.